ANALISA PENGARUH LAMPU JALAN TERHADAP INDEKS TINGKAT PELAYANAN JALAN DENGAN PERBANDINGAN METODE GREENSHIELD DAN METODE GREENBERG - Muklis Muklis; Revianty Nurmeyliandari (FORUM MEKANIKA, 2016)
This study aims to analyze the index level of service during the day and evening using street lights. Index level of service is analized with Greenshield method and Greenberg method, implemented in good condition or smooth road pavement, freeway, a few turn, and has a street light which function optimally. Thus do the analysis of vehicle speed in the afternoon and evening, and by using both methods can be analyzed index level of service